2009
DOI: 10.1128/jb.00881-08
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Plays a Beneficial Role in Membrane Organization and Cell Division of a Cold-Adapted Bacterium,Shewanella livingstonensisAc10

Abstract: Shewanella livingstonensis Ac10, a psychrotrophic gram-negative bacterium isolated from Antarctic seawater, produces eicosapentaenoic acid (EPA) as a component of phospholipids at low temperatures. EPA constitutes about 5% of the total fatty acids of cells grown at 4°C. We found that five genes, termed orf2, orf5, orf6, orf7, and orf8, are specifically required for the synthesis of EPA by targeted disruption of the respective genes. The mutants lacking EPA showed significant growth retardation at 4°C but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 38 publications
2
75
0
Order By: Relevance
“…Fax: +81-3-5317-9433; E-mail: htamegai@chs.nihon-u.ac.jp psychrophile, Shewanella livingstonensis Ac10, the amount of EPA in the membrane lipid increased when the organism was cultured at lower temperatures, such as 4 C, and an EPA-deficient mutant of Ac10 was found to be cold-sensitive. 11,12) S. violacea DSS12 contains high levels of EPA (15% of total fatty acids) in its membrane, 2) and the EPA-deficient mutant of S. violacea showed slow growth (Kawamoto et al, manuscript in preparation). In addition, UFAs might play important roles in the piezophilic property of the bacteria.…”
mentioning
confidence: 99%
“…Fax: +81-3-5317-9433; E-mail: htamegai@chs.nihon-u.ac.jp psychrophile, Shewanella livingstonensis Ac10, the amount of EPA in the membrane lipid increased when the organism was cultured at lower temperatures, such as 4 C, and an EPA-deficient mutant of Ac10 was found to be cold-sensitive. 11,12) S. violacea DSS12 contains high levels of EPA (15% of total fatty acids) in its membrane, 2) and the EPA-deficient mutant of S. violacea showed slow growth (Kawamoto et al, manuscript in preparation). In addition, UFAs might play important roles in the piezophilic property of the bacteria.…”
mentioning
confidence: 99%
“…Bacterial Strain and Growth Conditions-The EPA-less mutant of S. livingstonensis Ac10 used in this study was constructed by the disruption of orf5, one of the genes required for EPA synthesis (13). We previously found that this EPA-less mutant is longer than the wild-type strain because of retardation of cell division after DNA replication; this longer bacterial length facilitates microscopic analysis of the phospholipid subcellular localization, as fluorescence microscopic analysis of the much shorter wild-type strain cells is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…1; see supplemental "Experimental Procedures" for the synthesis). In these phospholipids, OLA (9-cis-18:1) was introduced into the sn-1 position because OLA and OLA-containing phospholipids were shown to have neutral effects on the phenotype of the EPA-less mutant (13,15).…”
Section: Fate Of Fluorescence-labeled Diacyl Phospholipids In Cellmentioning
confidence: 99%
See 2 more Smart Citations